Háziméh-repellens illatanyagok vizsgálata kukoricamoly illatanyag csapdákban - Májer, Péter; Szarukán, István; Szalárdi , Tímea; Tóth, Miklós; Nagy, Antal (GEORGIKON FOR AGRICULTURE, 2020)
Tests on the effectiveness of different honeybee repellent compounds have been made by researchers of the Plant Protection Institute of University of Debrecen and Plant Protection Institute, CAR since 2017. The goal is to exclude honeybees from bisexual European corn borer (Ostrinia nubilalis Hübn.) traps containing phenylacetaldehyde and 4-methoxyphenethyl alcohol. Compounds already tested have not so far achieved the desired effect in the experiments. That’s why the idea of testing alternative methods came up. In 2019 experiments were carried out in Napkor and other two sites, where 6 treatments were tested with unbaited control in 5 replicates. Repellent compounds in combination with basic European corn borer bisexual bait, coloured and mechanically modified traps were tested considering O. nubilalis, honeybees and Bombus spp. catches. Beyond that two kinds of basic lure made with 4-methoxyphenethyl alcohol from different sources also were compared. Based on our results development of coloured and mechanically modified (punched) traps are the most promising for further investigations.
Keywords: bait; attractant; honeybees; bumblebee; European corn borer